3 dimension (3D) anaglyph video application in teaching and learning / Muhammad Isha Ismail ... [et al.] - Ismail, Muhammad Isha; Mohd Latib, Farah Wahida; Rosli, Siti Hawa; Ab. Rahman, Nurul Farraheeda; Derahman, Adnan (2015)
The process of teaching and learning (T & L) in a classroom requires full cooperation between lecturers and students. To attract students to understand the topic, the lecturer needs to be more creative and innovative. Most of the students are less interested when lecturers teach subjects that require better reading, subjects that require imagination, or a subject that involves understanding the theory. Therefore, the Faculty of Civil Engineering of UiTM Pahang considers this issue as very important in ensuring students are more focused and enthusiastic in understanding such subjects. Using video in the T & L is one of the proven methods to attract students and facilitate them to understand the contents to be conveyed. However, the improvement of existing videos into 3D versions raises the student's interest and focus in the classroom. The main objective of this method is adopted to provide variety for the students in Faculty of Civil Engineering of UiTM Pahang contents in the classroom learning environment, making more interactive and increase their desire to explain that the topics taught. Production of special 3D glasses together in the classroom proves this method not only improves the characteristics of cognitive, but affective and phychomotor characteristics were also awakened. The feedback received from the students, also in the form of an automatically processed web-based questionnaire, reveals that the 3D anaglyph meets the main course objective to familiarize the students with modern technologies without losing focus to the physical engineering problem studied.